Can a bank crisis break your heart? - Meissner Christopher M; Stuckler David; King Lawrence P (BMC, 2008)
Abstract Background To assess whether a banking system crisis increases short-term population cardiovascular mortality rates. Methods International, longitudinal multivariate regression analysis of cardiovascular disease mortality data from 1960 to 2002 Results A system-wide banking crisis increases population heart disease mortality rates by 6.4% (95% CI: 2.5% to 10.2%, p < 0.01) in high income countries, after controlling for economic change, macroeconomic instability, and population age and social distribution. The estimated effect is nearly four times as large in low income countries. Conclusion Banking crises are a significant determinant of short-term increases in heart disease mortality rates, and may have more severe consequences for developing countries.